PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN NET INTEREST MARGIN (NIM) TERHADAP RETURN SAHAM PERBANKAN DI ASEAN EXCHANGE - Nandari, Bulan; Adam, Mohamad; Yuliani, Yuliani (Gapenas Publisher, 2025)
This research aims to determine the influence of Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) on the stock return of banking companies listed on the ASEAN Exchange. This research uses a quantitative research approach with secondary data sources. The population in this study includes all banking companies listed on the ASEAN Exchange for the period 2019-2023. The sample selection in this study used a non-random sampling technique with purposive sampling, resulting in a total of 230 samples after applying the sample criteria. The data analysis technique used in this research is panel data regression analysis, with the Common Effect Model (CEM) being the best-fit model. The results of this study indicate that Return on Assets (ROA) and Return on Equity (ROE) do not have a significant effect on the stock returns of banking companies on the ASEAN Exchange, while Net Interest Margin (NIM) has a significant positive effect on the stock return of banking companies on the ASEAN Exchange for the period 2019-2023